Effects of predation risks of bats on the growth, development, reproduction, and hormone levels of Spodoptera litura - Zhang, Wenjun; Liu, Yingying; Wang, Zhiqiang; Lin, Tingting; Feng, Jiang; Jiang, Tinglei (Frontiers in Ecology and Evolution, 2023)
Predation is a powerful selection pressure that shapes predator-prey interactions. Due to long-term interactions, moths have developed hearing to detect the echolocation calls of bats. This allows bats to impose the non-consumptive effects of predation on moths. However, information on the changes in the growth, development, reproduction, and hormones of moths that are vulnerable to bat predation is limited. In this study, we used Spodoptera litura (Lepidoptera: Noctuidae) to determine the effects of the predation risks of bats on their growth, development, reproduction, and hormone titers. Our results showed that the larvae of S. litura increased food intake, accelerated the development of the larval stages, increased mortality and metamorphosis failure, and had a smaller body size under the risk of predation by bats. Additionally, the reproductive activity and fecundity decreased in the adults of S. litura, but the juvenile hormone titers and 20-Ecdydysone hormone titers increased. These results suggested an adaptive response in S. litura under bat predation risks at the cost of lower survival and reproduction. Finally, we found that S. litura moths showed different responses to different predation risk cues, which suggested that they might assess the magnitude of different predation risks to make the most suitable decision for survival and reproduction. Our results highlighted the importance of the predation risk imposed by bats to negatively regulate the population dynamics of moths. Our findings indicated that the biological control of bugs using bats is a promising strategy.